The semantics of words дитя, дитина as a representant of qualificational characteristics of age - Гурова, Оксана Модестівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
On the basis of the analysis of different linguistic material presented in various types of linguistic dictionaries, ethnographic collections, the author of the article has revealed features of the semantics of words дитя, дитина in the context of common perceptions about stratifications of age periods of human life; has traced the word creative performance of roots -дит-/-діт-; has drawn attention to the estimate potential of generated word forms; has clarified the semantic structure of word дитина as a component of lexical-semantic organization of modern Ukrainian literary language; has identified and considered the reflection of original semantic potential in the semantics of the word дитя.